An empirical study on perception and attitude of employees towards HRD practices with special reference to Western Coalfields Ltd., Nagpur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There will be a positive impact on the enterprise if the HRD practices are perceived in a positive sense by the employees. Similarly, the employees will have positive attitude towards the management if they are satisfied with the HRD practices. If they are not satisfied, they will have negative attitude and this will affect their job satisfaction, which they derive from the organization. HRD practices influences job satisfaction among the employees, where HRD practices includes Recruitment and Selection procedure, Training and Development Compensation methods, General working conditions, Amenities available, Perquisites and other facilities provided by the organization.Aim: This study is focused on studying the perception and attitude of employees working in Western Coalfields Ltd, Nagpur towards Human Resource Development practices applied in their organization.Method: The study is performed by using descriptive type of methodology. The study depends on both primary as well as secondary data. The data collected from 100 employees of WCL by using well-structured questionnaire constitute the primary data. The information gathered through books, journals, magazines, reports, dailies consists of secondary data. The data collected are scrutinized, edited and tabulated.Conclusion: It is concluded that the HRD practices applied by WCL have profound impact on employee’s psychology and motivates them towards their job in a creditable manner. It is also known that the management of WCL is taking determined efforts in solving the problems of employees with its own grievances redressal cell